PERBANYAKAN IN VITRO KELADI TIKUS (Typhonium flagelliforme (Lodd) BI.), TANAMANA YANG BERPOTENSI SEBAGAI OBAT KANKER - Imelda, Maria (BERITA BIOLOGI, 2003)
Keladi tikusÂ (Typhonium flagelliforme (Lodd) BI.) of the Araceae generally grows wild in the open or in slightly shaded areas. The active compounds of the plant have not yet been known, however its potential for cancer medication has been reported by several media. Since the plant is being hevaly removed in their habitat, research for adoption of in vitro technique for production of their planting materilals is needed. Lateral shoots of a 2-cm tuber, were sterilized with 30% sodium hypochlorite for 15 minutes. After several rinses with sterile distilled water, the shoots were cultured on a soild Murashige & Skoog (MS) medium supplemented with BAP (0,25;0,5;0,75;1,0 mg/l) in combination with IBA (0,25;0,5;0,75;1,0 mg/l). All cultures were incubated at 26 C under fluorestcent lights of 16 hours/day. Rooting of shoots was induced on MS medium without growth regulators and the plantets were established in a potting medium of sand,compost and soil (1:1:1). The result showed that the highest rate of shoot proliferation and growth was on MS medium supplemented with 0,5 mg/l 1 BAP and 0.25 mg/l IBA. Using this medium, Â a sixteen-fold increase in shoot multiplication can be achieved with survival rate of 95%.